Phylogeography and phylogeny of the genus Acanthonyx (Decapoda, Epialtidae) in the north‐east Atlantic and Mediterranean. (12th February 2017) - Tavares, Ana I.; Cabezas, M. Pilar; Xavier, Raquel; Branco, Madalena; Lima, Fernando P.; Seabra, Rui; Ribeiro, Pedro A.; Lopes, Evandro P.; Santos, António M.
Abstract : The genus Acanthonyx Latreille, 1828 (Majoidea, Epialtidae) contains 17 or 18 known species, depending on competing taxonomic views, that are widely distributed across the world. Morphologically, most species look superficially alike, and therefore, similar taxonomic concepts have been described under different names. Consequently, there is today a considerable list of synonyms, which further complicates the taxonomy of the genus Acanthonyx . In this study, we conducted a phylogeographical and phylogenetic analysis of populations of the genus Acanthonyx in the NE Atlantic, Mediterranean and Macaronesia using the mitochondrial cytochrome oxidase subunit I (COI) and the nuclear 28S rRNA loci. Our phylogenetic and phylogeographical results revealed that Acanthonyx lunulatus sensu lato is a complex of three distinct lineages: one corresponding to the previously described Acanthonyx brevifrons, another to A. lunulatus sensu stricto and a third to a yet undescribed group. Whereas our results confirms that A. brevifrons deserves the status of a species, as it can be easily distinguishable from A. lunulatus by a few morphological traits, we could not find any such traits suitable for the discrimination between A. lunulatus sensu stricto and the third lineage. Furthermore, the degree of COI divergence between this lineage and A. lunulatus is below average levels for Decapoda species. Yet, no shared haplotypes have been detected between them. The differences found in the nuclear gene (indels), together with the sympatric occurrence of the two forms, prompt for a more detailed analysis of this group. Overall, the results show that significant genetic differentiation between specimens with similar morphology occurs in the Epialtidae, thus reinforcing the importance of combining morphological and genetic tools to fully resolve the taxonomy of these decapods.